2006
DOI: 10.1073/pnas.0510506103
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of docking interactions between ERK2 and MAP kinase phosphatase 3

Abstract: Mitogen-activated protein (MAP) kinases are central components of signal transduction pathways for cell proliferation, stress responses, and differentiation. Signaling efficiency and specificity are modulated in large part by docking interactions between individual MAP kinase and the kinase interaction motif (KIM), (R͞K) 2-3-X1-6-⌽A-X-⌽B, in its cognate kinases, phosphatases, scaffolding proteins, and substrates. We have determined the crystal structure of extracellular signal-regulated protein kinase 2 bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 35 publications
6
113
2
2
Order By: Relevance
“…positively charged amino acids in the D site form electrostatic interactions with the negatively charged portion of the DRS. Downstream, a C-terminal hydrophobic motif forms contacts with the DRS hydrophobic groove (15,29,30). Notably, in most D site-ERK interactions, a leucine residue in this C-terminal hydrophobic motif is buried in the DRS hydrophobic pocket.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…positively charged amino acids in the D site form electrostatic interactions with the negatively charged portion of the DRS. Downstream, a C-terminal hydrophobic motif forms contacts with the DRS hydrophobic groove (15,29,30). Notably, in most D site-ERK interactions, a leucine residue in this C-terminal hydrophobic motif is buried in the DRS hydrophobic pocket.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures of ERK in complex with its binding partners (28)(29)(30)(31)(32)(33) provide invaluable insights, many of which formed the basis of this study. However, the ability to form crystals of a complex is not guaranteed, and most of the structures of ERK complexes use linear peptides derived from the ERK-interacting molecules instead of structured proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that rather than displacing Ets-1 through an allosteric mechanism this peptide directly competes with Ets-1 for the DRS of ERK2. The basis for this hypothesis was the observation that the structural transitions that accompany the binding of a D-site peptide to the DRS of ERK2 (15,16) are very similar to those that occur upon the conversion of ERK2 from the unactivated to the activated form upon MKK1-mediated phosphorylation (33). Thus, we reasoned that, if Ets-1 binds both major conformations of ERK2, the most likely explanation that the D-site peptide displaces Ets-1 from ERK2 is that it occupies part of the Ets-1 binding site.…”
Section: Resultsmentioning
confidence: 99%
“…The best described docking motif is known as docking site for ERK and JNK (DEJL) or D motif (Chang et al, 2002;Lee et al, 2004;Callaway et al, 2005;Zhou et al, 2006) which posses the general pattern (Arg/Lys) 1À2 -(X) 2-6 -+ A -X-+ B , where + A and + B are hydrophobic residuesleucine (Leu), isoleucine (Ile) or valine (Val). Crystal structures of MAPK complexes with peptides derived from upstream and downstream targets having these DEJL motifs (e.g., ERK2 with MAPK phosphatase 3 (MK3) or with the hematopoietic tyrosine phosphatase (HePTP)); p38a with the transcription factor myocyte enhancer factor (MEF)2 or the p38 MAPKK, MKK3B; and JNK1 with the scaffold Jun interacting protein 1 (JIP1) (Chang et al, 2002;Heo et al, 2004;Zhou et al, 2006;Liu et al, 2006b) have revealed that the MAPK binding site for the DEJL motif is similar among the different groups of MAPKs, comprising an hydrophobic grove between helices aD, aE and the b7-b8 reverse turn and an acidic patch that binds the positive amino acids within the DEJL motif of the partner protein (Figure 1). …”
Section: The Structure Of Mapksmentioning
confidence: 99%
“…In this regard, the comparison of the structure of different MAPK complexes has revealed that changes in the amino-acid composition of MAPK docking binding regions can determine the binding selectivity (Chang et al, 2002;Heo et al, 2004;Zhou et al, 2006;Liu et al, 2006b) (Figure 1). Moreover, recent studies have provided insights into the dynamic conformational changes occurring on MAPKs upon binding to upstream activators, scaffolds and downstream targets (Heo et al, 2004;Hoofnagle et al, 2004;Lee et al, 2005;Zhou et al, 2006), which can also contribute to the signaling specificity of each MAPK module.…”
Section: The Structure Of Mapksmentioning
confidence: 99%